a. Dereceden Cesaro ve istatistiksel türev - Ari, Ayşenur Güneş (Muş Alparslan Üniversitesi, 2022)
İstatistiksel yakınsaklık Toplanabilme Teorisi'nde ve Fonksiyonel Analiz'de büyük öneme sahiptir. Literatürde istatistiksel yakınsaklık kavramlarının üzerine yakın tarihte Cesaro türevi ve istatistiksel türev kavramları kazandırılmıştır. Bu çalışmada ise ?. dereceden Cesaro ve istatistiksel türev kavramı tanımlanarak bazı yeni sonuçlar elde edilmiştir. Bu kısımlar verilmeden önce ise istatistiksel yakınsaklık ve Cesaro türevi ile ilgili kavram ve teoremler ifade edilecektir.

Statistical convergence is of great importance in Summability Theory and Functional Analysis. On top of the statistical convergence concepts in the literature, Cesaro Derivative and statistical derivative concepts have been introduced recently. In this study, ?. Grade Cesaro Derivative and statistical derivative concepts are defined and some results are discussed. Before these parts are given, the concepts are given, the concepts and theorems related to statistical convergence and Cesaro derivative will be expressed.
a. Degrees Cesaro and statistical derivative
Keywords: Matematik; Mathematics